Depression, anxiety and stress severities in multiple sclerosis patients using injectable versus oral treatments. (July 2017) - Al-Hussain, Fawaz; Al-Salloum, Noura; Alazwary, Naael; Saeedi, Jameelah; Howaidi, Sara; Daif, Abdulkader
Aim: Studies on multiple sclerosis in Saudi Arabia remain scant, particularly studies on the psychological aspects. This study measures severities of depression, anxiety and stress, and compares them to the used disease-modifying treatment.Materials & methods: Cross-sectional study using a phone questionnaire targeting 452 Saudi patients with relapsing-remitting multiple sclerosis following in King Khalid University Hospital, King Fahad Medical City or Security Forces Hospital.Results: From 235 patients, 149 used interferons, 58 used fingolimod and 28 used natalizumab. Depression scores were similar among all demographic and drug groups. Interferons versus fingolimod anxiety scores were significantly different (p = 0.035). Stress scores were within normal limits.Conclusion: Mild anxiety was higher among interferon users, which could be due to injection anxiety reasons.